SAT0040 Macroscopic Scores of Synovitis at Knee Arthroscopy Correlate well with CRP, Inflammatory Histology Findings, And can Predict Later Erosive Disease on Hands and Feet Plain Film Radiographs. (9th June 2015) - Orr, C.; McGarry, T.; Young, F.; Linehan, E.; Fearon, U.; Veale, D.J.
Abstract : Background: The utility of synovial biopsy has been confirmed as an important research tool in increasing our understanding of the pathogenesis of RA, evaluating new treatments and identifying potential therapeutic targets. 1, 2 The utility of this safe and well-tolerated minimally invasive investigation in routine clinical practice is less well established, but in selected cases it can be useful in diagnosis. 3 How macroscopic scores of synovitis as graded by the operator at arthroscopy relate to histology findings of the synovial biopsies retrieved has not been previously reported. Furthermore, the opportunity that macroscopic findings at arthroscopy may have to allow stratification of patients into disease phenotypes with respect to progression of erosive disease has not been reported. Objectives: To examine how macroscopic scores of synovitis relate to CRP, histology findings and bone erosions. Methods: A macroscopic score of synovitis, graded at 5 unit intervals between 0-100, is recorded by the operator at arthroscopy. How this score relates to the variables described below was examined in a cohort of 111 RA patients who underwent arthroscopy. The Wilcoxon matched-paired signed rank test was employed to test for a correlation between serum CRP concentrations at the time of arthroscopy, and synovitis scores. The Chi-squared test was employed to test for a correlation between categorical synovitis scores (4 quartiles), and categorical data for histology findings (no inflammation, mild inflammation, and moderate-severe inflammation) and the presence or absence of erosions on plain film radiographs of hands and feet. Results: A strong correlation was observed between synovitis scores and CRP (n=103, p<0.001). Higher synovitis scores correlated with inflammatory findings on histology (n=90, p=0.02), and with the presence of erosions on radiographs (n=96, P=0.01). There was also a strong correlation between CRP at time of arthroscopy and histology findings (n=87, p=0.009). Conclusions: We have demonstrated that synovitis can be reliably assessed by scores, by demonstrating a correlation with a systemic marker of inflammation and microscopic findings. Furthermore, those with high synovitis scores are more likely to have erosions on later radiographs. This demonstrates that arthroscopy is clearly a useful diagnostic investigation for patients in where it is not clear whether there is synovitis, and in assisting to stratify those who may have a worse disease phenotype. References: Gerlag DM, Tak PP. Novel approaches for the treatment of rheumatoid arthritis: lessons from the evaluation of synovial biomarkers in clinical trials. Best Practice & Research Clinical Rheumatology. 2008;22(2):311-23. Kraan MC, Reece RJ, et al. Modulation of inflammation and metalloproteinase expression in synovial tissue by leflunomide and methotrexate in patients with active rheumatoid arthritis: Findings in a prospective, randomized, double-blind, parallel-design clinical trial in thirty-nine patients at two centers. Arthritis & Rheumatism. 2000;43(8):1820-30. Bresnihan B. Are synovial biopsies of diagnostic value? Arthritis Research and Therapy 5, no. 6 (2003): 271-278. Disclosure of Interest: None declared